Investigating students’ perspectives on the use of Quizziz as a teaching tool in accounting classroom - Saat, Natasya (Journal of Islamic, Social, Economics and Development, 2025)
This study examines students' perspectives on using Quizizz as an educational tool in teaching accounting subjects. Although technology integration in higher education is on the rise, accounting classrooms still see limited adoption of such tools. Focusing on Foundation in Business students at Heriot-Watt University Malaysia, the study employed a random sampling survey conducted online via Google Forms at the end of the semester, incorporating both open-ended and closed-ended questions. Descriptive analysis of the data collected revealed that Quizizz significantly improved students’ understanding of accounting concepts and enriched the teaching and learning experience. By promoting interactive learning, immediate feedback, and active engagement, Quizizz enhances student motivation and knowledge retention when paired with traditional teaching methods. While its effectiveness may vary depending on the topic and student preferences, Quizizz proves to be a valuable addition to accounting education. Future research should explore how the competitive nature of Quizizz affects students’ stress and learning across different personality types and disciplines to better understand its overall effectiveness and applicability in higher education